The Effectiveness of Humanistic Counseling Using Play-Based Learning Techniques to Improve Emotional Management and Social Communication Skills in Early Childhood - Arny Bana; I Ketut Gading (Department of Guidance and Counseling, FIP, Undiksha, 2025)
The low ability of students to manage the learning process independently and the existence of negative perceptions of themselves are the main factors in decreasing academic achievement and self-confidence. This study aims to test the effectiveness of cognitive behavioral counseling with cognitive restructuring techniques in improving self-regulation in learning and students' self-concept. This study used a quasi-experimental design with a pretest-posttest control group design model. The subjects consisted of 68 students who were divided into two groups, namely the experimental group that received intervention and the control group without treatment. The research instrument was a self-regulation questionnaire in learning and self-concept that had been tested for validity and reliability. Data analysis used MANOVA to determine the difference in pretest and posttest scores on both variables. The results showed that cognitive behavioral counseling with cognitive restructuring techniques was effective in improving self-regulation in learning and students' self-concept simultaneously (p <0.05). These findings strengthen the effectiveness of cognitive restructuring techniques in the context of guidance and counseling services, especially in schools with lower middle socioeconomic backgrounds. This study also provides theoretical and practical contributions to the development of counseling services based on the cognitive behavioral approach in educational environments.